Screeing for cytotoxicity and anti-diabetic studies on michelia alba - Jibby, Jinang. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Michelia alba DC (Magnoliaceae) is an important medicinal plant. An ethyl acetate extract and a methanol extract of the leaves of Michelia alba showed toxicity against the Artemia salina larvae. Both extract showed LDso value at the concentration of 100 llg/mL. Antidiabetic study done to the aqueous extract of the leaves of Michelia alba using Chinese hamster showed that there was a significant anti-diabetic activity.